WORD-FORMATION PROCESSES IN LOC’S SITE POEM: MORPHOLOGICAL STUDY - Rifky Sultan Nico Sembiring; M. Handika Syahputra; Raudah Raudah; Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2023)
This study aims to find out the processes of word formation in ten poems in the LOC’s Site Poem. Word-formation processes is the study in morphology. The method used is qualitative research. The data are from the ten poems in the LOC’s Site Poem. The results of the study are that there are 193 (one hundred and ninety three) data found in the LOCs Site Poem. The affixation process including inflectinal and derivational process by 87.56% (eighty seven point five six percent), compounding process by 9.84% (nine point eight four percent), and acronym by 2.07%(two point oh seven percent). The dominant word formation process appear is affixation of inflectional process. The compounding is the combination of noun plus noun and adjective or adverb plus noun.